Ivy + Bean - Barrows, Annie; Blackall, Sophie (San Francisco : Chronicle Books, 2006)
When seven-year-old Bean plays a mean trick on her sister, she finds unexpected support for her antics from Ivy, the new neighbor, who is less boring than Bean first suspected.
510
Accelerated Reader AR
Keywords: Friendship -- Fiction; Neighbors -- Fiction; Sisters -- Fiction